Radiocarbon Dating of Leaf Waxes in the Loess-Paleosol Sequence Kurtak, Central Siberia. Issue 1 (6th February 2017) - Haas, Mischa; Bliedtner, Marcel; Borodynkin, Igor; Salazar, Gary; Szidat, Sönke; Eglinton, Timothy Ian; Zech, Roland
Abstract: Loess-paleosol sequences (LPS) are valuable archives for Quaternary climate and environmental changes. So far, LPS are generally dated using luminescence, with ~10% uncertainties, or radiocarbon ( 14 C) analyses in the rare cases that charcoal or macrofossils are available. For this study, we determined 14 C ages of leaf waxes (long-chain n -alkanes) extracted from the LPS Kurtak in central Siberia. 14 C ages range from 16.7 to 22.9 ka cal BP for the last glacial loess and from 24.5 to 35.3 ka cal BP for the paleosol correlated with marine isotope stage (MIS) 3. Overall, this is in good agreement with independent age control based on stratigraphy, infrared stimulated luminescence (IRSL) dating, and 14 C dating on charcoal and macrofossils. However, strong cryoturbation and solifluction seem to have affected the MIS 3 paleosol early during MIS 2. Our results corroborate the stratigraphic integrity of leaf waxes, and highlight their potential for dating LPS back to ~35–40 ka BP. Compared to compound-specific 14 C analyses, which are very time-consuming and require specialized instrumentation (gas chromatograph with fraction collector), 14 C dating of leaf waxes as a whole compound class is relatively quick and straightforward and warrants further investigation as a chronological tool.